Knowledge, Attitude and Practice of Final Year Medical Students and Interns on Diabetic Retinopathy in Saudi Arabia - Saad H. Alenezi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetic retinopathy (DR) is a preventable complication of uncontrolled diabetes. Following the guidelines in timely evaluation and treatment can delay the onset and slow disease progression. Therefore, medical students should have adequate knowledge, attitude, and practice (KAP) towards DR in preparation for their medical practice after graduation. Aim: To evaluate the Knowledge Attitude and practices (KAP) among final year medical students and interns in College of Medicine, Majmaah University, Saudi Arabia. Design: A cross-sectional approach with a self-administered questionnaire. Methods: Following ethical and administration approval, a link with the questionnaire, generated on Google Forms, was distributed among final year medical students and interns at College of Medicine, Majmaah University. The total number of students was retrieved to be 120, where 80 students participated in this study to yield a response rate of 66%. Results: Out of the 80 participants, 57.5% were in their internship, 71.25% were male, and 61.25% were aged 25 years or older. In terms of KAP, the knowledge score was borderline 3.95 (SD=1.06), while attitude and practice scores were good, scoring 7.45 (SD=0.93) and 2.17 (SD=0.72), respectively. The final-year medical students were significantly more knowledgeable about this condition than the interns and the common cause of visual impairment in patients with DR. No significant difference was noted in attitude or practice between the study groups. Conclusion: Knowledge regarding DR was acceptable in final year medical students of College of Medicine. Future practicing physicians should be well educated about the methods to preserve vision among this patient population, especially in a resourceful setting with limited barriers to optimal practice.